Histological and immunohistochemical features of the spleen in persistent polyclonal B-cell lymphocytosis closely mimic splenic B-cell lymphoma - Sun Ping; Juskevicius Ridas (BMC, 2012)
Abstract Persistent polyclonal B-cell lymphocytosis (PPBL) is rare and intriguing hematological disorder predominantly reported in young to middle- aged smoking women. It is characterized by persistent moderate polyclonal B-cell lymphocytosis with circulating hallmark binucleated lymphocytes and elevated polyclonal serum IgM. Most patients have benign clinical course on long-term follow-up. Some pathologic features of PPBL may resemble malignant lymphoma, including morphology as well as frequent cytogenetic and molecular abnormalities. Significant symptomatic splenomegaly requiring splenectomy is very unusual for this disorder; therefore there is a lack of descriptions of the morphologic features of the spleen in the literature. We present here one of the first detailed descriptions of the morphologic and immunohistochemical features of the spleen from a young female with PPBL who developed massive splenomegaly during 6-year follow up. Splenectomy was performed for symptomatic relief and suspicion of malignant process. The morphological and immunohistochemical features of the spleen closely mimicked involvement by B-cell lymphoma, however there was no monotypic surface light chain restriction seen by flow cytometry and no clonal rearrangement of IgH gene was detected by molecular analysis. Evaluating a splenectomy sample in cases like this may present a diagnostic challenge to pathologists. Therefore, correlation with B cell clonality studies (by flow cytometry and molecular analysis), clinical findings and peripheral blood morphology searching for characteristic binucleated lymphocytes is essential to avoid misdiagnosing this benign process as B-cell lymphoma. We also present here a literature review on pathogenesis of PPBL. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/5329558967545656